2021
DOI: 10.1097/inf.0000000000003293
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes and Antibody Response in COVID-19–Positive Pediatric Solid Organ Transplant Recipients

Abstract: We describe the clinical and laboratory manifestations and outcomes of 25 pediatric solid organ transplant recipients who tested positive for severe acute respiratory coronavirus-2. Twenty-one (84%) developed a mild disease; 22 of 23 (96%) had a positive serologic response. Two patients (8%), both kidney transplant recipients with additional comorbidities, developed a severe disease. The findings emphasize the need for close monitoring of this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…As for pediatric solid organ transplant (SOT) recipients, Talgam-Horshi et al revealed a 96% seroconversion rate among 25 patients. However, they did not present the antibody levels or compare them with a control group [14]. Meanwhile, researchers from Saudi Arabia observed eight pediatric kidney transplant (PKT) recipients and showed their ability to maintain detectable levels of antibodies at a median follow-up time of 75 days [15].…”
Section: Discussionmentioning
confidence: 99%
“…As for pediatric solid organ transplant (SOT) recipients, Talgam-Horshi et al revealed a 96% seroconversion rate among 25 patients. However, they did not present the antibody levels or compare them with a control group [14]. Meanwhile, researchers from Saudi Arabia observed eight pediatric kidney transplant (PKT) recipients and showed their ability to maintain detectable levels of antibodies at a median follow-up time of 75 days [15].…”
Section: Discussionmentioning
confidence: 99%
“…We report increased immunosuppression burden during the last 2 years of the study period, even though no formal change to the protocol was made. This trend of increased immunosuppression burden to improve allograft survival will have to be balanced with the increased risk for infections in pediatric patients, especially during the era of COVID‐19 infection and its implications on pediatric transplant recipients 31 …”
Section: Discussionmentioning
confidence: 99%
“…This trend of increased immunosuppression burden to improve allograft survival will have to be balanced with the increased risk for infections in pediatric patients, especially during the era of COVID-19 infection and its implications on pediatric transplant recipients. 31 In conclusion, in this retrospective study, we analyzed the frequency, risk factors, and outcomes of viremias in pediatric kidney transplant patients. We found an increasing incidence of viremias in more recent years.…”
Section: Discussionmentioning
confidence: 99%
“…Most pediatric SOT cohorts reported hospitalization in 15-25% of patients with only a minority (1-7%) needing ICU-level care and only a handful of deaths attributed to COVID-19. 15 , 28 , 29 , 30 , 31 , 32 , 33 These cohorts principally included patients identified during the first waves of infection. The more recent Delta and Omicron variants have had greater impact on children.…”
Section: Introduction On Covid-19mentioning
confidence: 99%
“…To date the published literature on use of remdesivir, glucocorticoids and monoclonal antibodies for COVID-19 is limited to a case report of two pediatric SOT recipients hospitalized with COVID-19 who recovered after treatment with dexamethasone. 29 Several organizations including the National Institutes of Health have developed evidence-based guidance documents for prevention and treatment of COVID-19. 26 Based on these guidance documents and the reported epidemiology in SOT to date, organizations such as the Society for Pediatric Liver Transplantation and the American Society of Transplantation (AST), have extrapolated therapy recommendations to SOT recipients including the use of antivirals, glucocorticoids and monoclonal antibody preparations as locally available.…”
Section: Introduction On Covid-19mentioning
confidence: 99%